Inhibition Role of Atherogenic Diet on Ethyl Carbamate Induced Lung Tumorigenesis in C57BL/6J Mice - Chen, Ting (Sci Rep, 2017)
With emerging evidence connecting cholesterol dysregulation with disturbed pulmonary homeostasis, we are wondering if diet induced hypercholesterolemia would influence the susceptibility to chemical induced lung tumorigenesis in mice. Six to eight week-old male C57BL/6J mice were fed with either a high-cholesterol atherogenic diet (HCD) or matching normal diet (ND), respectively. Following 3 weeks diet adapting, a multi-dose intraperitoneal injections of ethyl carbamate (urethane, 1 g/kg body weight) were established and lung tumorigenesis assessments were taken after 15 weeks latency period. Compared to the urethane treated ND-fed mice, the HCD-fed mice exhibited significantly decreased lung tumor multiplicity and attenuated pulmonary inflammation, which including reduced influx of leukocytes and down regulated tumor-promoting cyto-/chemokine profile in bronchoalveolar lavage fluid, decreased TLR2/4 expression and NF-κB activation in the lung. As a sensor regulating intracellular cholesterol homeostasis, nuclear receptor LXR-α was up-regulated significantly in the urethane treated HCD-fed mice lungs compared to the ND-fed mice lungs, accompanied with decreased pulmonary free cholesterol content and suppressed tumor cell proliferation. These results suggested that intrapulmonary cholesterol homeostasis, other than systematic cholesterol level, is important in lung tumorigenesis, and LXR activation might partly contribute to the inhibitory role of atherogenic diet on lung tumorigenesis.